Localization of gamma-tubulin in interphase and mitotic cells of a unicellular eukaryote, Giardia intestinalis - Nohýnkova, E; Dráber, P; Reischig, J; Kulda, J (European journal of cell biology, 2000)
Giardia intestinalis, a bi-nucleated amitochondrial flagellate, possesses a complex cytoskeleton based on several microtubular systems (flagella, adhesive disk, median body, funis, mitotic spindles). MTOCs of the individual systems have not been fully defined. By using monoclonal antibodies against a conserved synthetic peptide from the C-terminus of human gamma-tubulin we investigated occurrence and distribution of gamma-tubulin in interphase and mitotic Giardia cells. On the immunoblots of Giardia cytoskeletal extracts the antibodies bound to a single polypeptide of approximately 50 kDa. Immunostaining of the interphase cell demonstrated gamma-tubulin as four bright spots at the basis of four out of eight flagella. Gamma-tubulin label was associated with perikinetosomal areas of the ventral and posterolateral pairs of flagella which are formed de novo during cell division. Basal body regions of the anterolateral and caudal pairs of flagella which persist during the division and are integrated into the flagellar systems of the daughter cells did not show gamma-tubulin staining. At early mitosis, gamma-tubulin spots disappeared reappearing again at late mitosis in accord with reorientation of parent flagella and reorganization of flagellar apparatus during cell division. The antibody-detectable gamma-tubulin epitope was absent at the poles of both mitotic spindles. Albendazole-treated Giardia, in which spindle assembly was completely inhibited, showed the same gamma-tubulin staining pattern thus confirming that the fluorescent label is exclusively located in the basal body regions. Our results point to a role of gamma-tubulin in nucleation of microtubules of newly formed flagella and indicate unusual mitotic spindle assembly. Moreover, the demonstration of gamma-tubulin in Giardia shows ubiquity of this protein through the evolutionary history of eukaryotes.
Keywords: Immunoglobulin G; monoklonální protilátky; Cell Nucleus; fluorescenční mikroskopie; Mitosis; Cytoskeleton; imunoglobulin G; buněčné jádro; elektroforéza v polyakrylamidovém gelu; Models, Biological; Interphase; interfáze; Immunoblotting; Animals; Electrophoresis, Polyacrylamide Gel; lidé; Microscopy, Fluorescence; biologické modely; Humans; zvířata; Giardia lamblia; cytoskelet; imunoblotting; mitóza; tubulin; Antibodies, Monoclonal; Tubulin